Red Media, Blue Media: Evidence of Ideological Selectivity in Media Use - Iyengar, Shanto; Hahn, Kyu S (Journal of communication, 2009)
We show that the demand for news varies with the perceived affinity of the news organization to the consumer’s political preferences. In an experimental setting, conservatives and Republicans preferred to read news reports attributed to Fox News and to avoid news from CNN and NPR. Democrats and liberals exhibited exactly the opposite syndrome—dividing their attention equally between CNN and NPR, but avoiding Fox News. This pattern of selective exposure based on partisan affinity held not only for news coverage of controversial issues but also for relatively “soft” subjects such as crime and travel. The tendency to select news based on anticipated agreement was also strengthened among more politically engaged partisans. Overall, these results suggest that the further proliferation of new media and enhanced media choices may contribute to the further polarization of the news audience. Resumen Los Medios Rojos, los Medios Azules: La Evidencia de la Selectividad Ideológica en el Uso de los Medios Mostramos que la demanda de noticias varía con la percepción de la afinidad con las organizaciones de noticias en las preferencias políticas del consumidor. En un ambiente experimental, conservadores y Republicanos prefirieron leer reportes de noticias atribuidos a la cadena de noticias Fox y evitaron las noticias de CNN y NPR. Los Demócratas y liberales exhibieron el síndrome exactamente opuesto – dividiendo su atención igualmente entre CNN y NPR, pero evitando las noticias de la cadena Fox. Esta pauta selectiva de exposición basada en la afinidad partidaria es sostenida no solo con respecto a la cobertura de noticias de hechos controversiales, sino también con respecto a materias relativamente “blandas” tales como el crimen y el viaje. La tendencia a seleccionar noticias basadas en un acuerdo anticipado fue aumentada también entre los partidarios políticamente más comprometidos. En general, los resultados sugieren que la mayor proliferación de los nuevos medios y las opciones mejoradas de los medios pueden contribuir a una mayor polarización de las audiencias de noticias. ZhaiYao Yo yak